Kemampuan Menulis Naskah Drama Berdasarkan Cerpen Siswa Kelas IX Semester Genap SMPN 19 Bandar Lampung - Permanasari, Dian (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The issues raised in this study relate to the ability of students to write literary works, especially in writing drama scripts based on short stories. Through the ability to write drama scripts based on short stories is expected to improve students' abilities in the field of literature in particular can change the short story into a drama that is as good as possible. This study aims to describe how the level of students' abilities in writing drama scripts based on short stories. To achieve the above research objectives, the authors use quantitative descriptive methods, with the sampling technique used is simple random sampling technique. The assessment indicators are: (1) theme, (2) figure, (3) setting, (4) flow, (5) dialogue, (6) language, (7) creativity. Based on the results of the study, it was found that the students' ability in writing drama scripts with seven indicators as a basis for assessment, the results or the average score obtained was 75 The score was obtained from the calculation of the number of acquisition scores.